Beyong Mirrors: Research Pathways (CeiDE 2013-2017) (Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls., 2018)

Education for justice-oriented and participatory citizenship in a politicized era in Hong Kong. (Handbook of Research on Education for Participative Citizenship and Global Prosperity, 2018)

Use of apparatuses in science laboratory: developmental characteristics of didactical interactions. (The International Education & Learning Review, 2018)

A content analysis of views of disability within Portuguese language newspapers in Macau - Amaral, Ana Helena (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Acoustic communication in marine shallow waters: testing the acoustic adaptive hypothesis in sand gobies - Amorim, Maria Clara P.; Vasconcelos, Raquel O.; Bolgan, Marta; Pedroso, Silvia S.; Fonseca, Paulo J. (Journal of Experimental Biology, 2018)
Skip to Next Section Acoustic communication is an important part of social behaviour of fish species that live or breed in shallow noisy waters. Previous studies have shown that some fish species exploit a quiet window in the background noise for communication. However, it remains to be examined whether hearing abilities and sound production of fish are adapted to marine habitats presenting high hydrodynamism. Here, we investigated whether the communication system of the painted (Pomatoschistus pictus) and the marbled (Pomatoschistus marmoratus) gobies is adapted to enhance sound transmission and reception in Atlantic shallow water environments. We recorded and measured the sound pressure levels of social vocalisations of both species, as well as snapshots of ambient noise of habitats characterised by different hydrodynamics. Hearing thresholds (in terms of both sound pressure and particle acceleration) and responses to conspecific signals were determined using the auditory evoked potential recording technique. We found that the peak frequency range (100–300 Hz) of acoustic signals matched the best hearing sensitivity in both species and appeared well adapted for short-range communication in Atlantic habitats. Sandy/rocky exposed beaches presented a quiet window, observable even during the breaking of moderate waves, coincident with the main sound frequencies and best hearing sensitivities of both species. Our data demonstrate that the hearing abilities of these gobies are well suited to detect conspecific sounds within typical interacting distances (a few body lengths) in Atlantic shallow waters. These findings lend support to the acoustic adaptive hypothesis, under the sensory drive framework, proposing that signals and perception systems coevolve to be effective within local environment constraints.

The study of financial valuation of Marriott International, Inc - Ao, Ka Ian (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of brand awareness for Mongolian Cashmere in Macau - Batsukh, Selenge (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

O português dos Tongas de São Tomé. In Oliveira, Márcia Santos Duarte; Araujo, Gabriel Antunes. (orgs.) O português na Africa atlântica - Baxter, A. N. (Humanitas/FAPESP, 2018)

Concordância verbal - Baxter, A. N.; Lopes, N. (Tânia Lobo (ed.) O português escrito por afro-brasileiros no século XIX: atas de reuniões da Sociedade Protetora dos Desvalidos, 2018)

Malacca Creole Portuguese in the 19th century: Evidence of a wider lectal range? - Baxter, Alan N. (Journal of Pidgin and Creole Languages, 2018)
Abstract Earlier linguistic research suggested that Malacca Creole Portuguese (MCP) had existed without diglossia with Portuguese ever since the Dutch conquest of Portuguese Malacca in 1642, yet it had experienced some contact with Portuguese in the 19th and 20th centuries. The present study adds significantly to this discussion. It considers a range of information from sociohistorical studies and archival sources (including linguistic data) relating to the Dutch (1642–1795, 1818–1823) and early British (1795–1818, 1823–1884) colonial periods. For the Dutch period, it is seen that contact with other Creole Portuguese communities is likely to have persisted for some time. Most significant, however, is the finding that 19th century texts in Portuguese and creole Portuguese, recently identified in archival sources in London and Graz, show that Portuguese continued to be part of the Malacca sociolinguistic setting until the early British period, and that missionary Indo-Portuguese also had a presence at that time. It is concluded that, rather than presenting a narrow lectal range akin to that of the MCP community in the late 20th century, the creole lectal grid in the 19th century was more complex, and included dimensions of a continuum in a diglossic relationship with Portuguese.

Syntactic and lexical typology of Macau Patuá and Malacca Creole Portuguese. - Baxter, Alan N. (University of Saint Joseph, 2018)

A Financial Evaluation of Fluor Corporation - Cabaça, Anacleto de Jesus da Silva (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish - Cardoso, Sara D.; Gonçalves, David; Goesmann, Alexander; Canário, Adelino V. M.; Oliveira, Rui F. (Molecular Ecology, 2018)
Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e., larger and older nest-holder males and smaller and younger sneaker males occur). Sneakers mimic both female's courtship behaviour and nuptial coloration to get access to nests and sneak fertilizations, and later in life transition into nest-holder males. Thus, this species offers the unique opportunity to study how the regulation of gene expression can contribute to intersex phenotypes and to the sequential expression of male and female behavioural phenotypes by the same individual. We found that at the whole brain level, expression of the sneaker tactic was paralleled by broader and divergent gene expression when compared to either females or nest-holder males, which were more similar between themselves. When looking at sex-biased transcripts, sneaker males are intersex rather than being either nest-holder or female-like, and their transcriptome is simultaneously demasculinized for nest-holder-biased transcripts and feminized for female-biased transcripts. These results indicate that evolutionary changes in reproductive plasticity can be achieved through regulation of gene expression, and in particular by varying the magnitude of expression of sex-biased genes, throughout the lifetime of the same individual.
Keywords: RNA-seq; Salaria pavo; alternative reproductive tactics; behavioural plasticity; neurogenomic state; sex-biased gene expression

Obediência militar, liberdade e consciência, Ética Aplicada: Política, Edições 70, - Carreiras, H.; Leandro, F. J. (2018)

Shopping styles of Chinese generation Y: luxury shopping in Macau - Chan Sai Lai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on the Anti-Money Laundering Systems in the banking sector in Macao: a case study of the practice of HSBC Macao - Chan, Ka Ian (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The psychological factors related to the usage of electronic devices among adolescents in Macau - Chan, Ka Pou (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a sub-tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2018)

A comparative analysis of smartphone brands in Macau: Apple and Samsung - Cheong, Ka Man (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The use of cognitive behavior child-centered play therapy: a case study - Cheong, Tania Guilherme (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

When the Gospel meets the China Dream: Religious Freedom and the Golden Rule - Chiaretto Yan, Kin Sheung (International Bulletin of Mission Research, 2018)
The issue of religious freedom affects Sino-Vatican relations, but the Roman Catholic Church shares values with Confucianism, which provides common ground for dialogue. Pope Francis is focusing the church outward by promoting a culture of encounter and by working unceasingly for a fraternal dialogue of peace. Chinese president Xi Jinping urges his people to fulfill the China dream, emphasizing the core values of harmony, friendship, and civilization. Many have believed that the Gospel can contribute to China?s spiritual civilization; normalization of relations between China and the Holy See would benefit China and the Catholic Church and contribute to world peace and harmony.

The influence of SAR government performance on people’s trust toward Central government: Implications for Hong Kong and Macau civic education - Chris Cheung, Hin Wah; So, Man Yum Larry; Choi, Chi U. Francis; Chow, Chin Fung Philip (Asian Education and Development Studies, 2018)
Purpose The purpose of this paper is to explore the influence of Special Administrative Region (SAR) performance on the “trust” of Hong Kong and Macau people, who “live” under similar context of “one country, two systems,” toward Beijing Central Government. The different perceptions, relating to the abovementioned issue, of the young peoples’ are also investigated. Implication for civic education in these two societies will be brought to light. Design/methodology/approach This study adopts secondary data analysis on the captioned topic. To further illustrate the said issue, this study reviews and analyzes data from protest campaigns in both societies. Findings This paper finds that the performance of Hong Kong and Macau SAR Governments has different impacts on the peoples’ “trust” toward Central Government. It may attribute to the different perceptions about the role of Central Government and levels of democratization in these societies. Civic education emphasizing the “core spirit” of “One country, two systems,” roles of SAR and Central Governments could enable young people better comprehend their relationship with Mainland China and their role as SAR–Chinese citizens. Originality/value This paper is an exploratory study for providing implications for further research on this topic.
Keywords: Civic education; Political trust

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls - Correia, Ana; Fernandes, Clara; Maia, João (Beyong mirrors: Research pathways (CeiDE 2013-2017), 2018)

Uma leitura de Monção,de Vimala Devi: O puzzle da identidade - Coutinho, Marilia Gomes Coelho (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Research Projects: Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (XIV Congresso de Geoquímica dos Países de Língua Portuguesa e XIX Semana de Geoquímica (XIV CGPLP/XIX SG, international conference, 2018)

A Confucian Perspective on Tertiary Education for the Common Good - Eh, Edmond (The Journal of the Macau Ricci Institute, 2018)
Confucian education is best captured by the programme described in the Great Learning. Education is presented first as the process of self-cultivation for the sake of developing virtuous character. Self-cultivation then ...

Inquérito aos estudantes da Universidade de São José: o peso da cultura na aprendizagem das línguas - Espadinha, M. A.; Borges, V. (A framework in Portuguese as a Foreign Language for Chinese Native Speakers, 2018)

Hacking: Toward a Creative Methodology for Cultural Institutions - Estadieu, G; Caires, C. S (2018)

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Postgraduate Certificate Program of Education in University of Saint Joseph: Cultivating the Rationales and Techniques of Culturally Responsive Teaching among Teachers in Macau (“聖若瑟大學學位後證書課程: 澳門教師文化关联教學理念和技能的培養”in Chinese) - Ge, Yun (University of Saint Joseph, 2018)

The Cultivation of Research Labor in Pacific Asia with Special Reference to Singapore - Ge, Yun; Ho, K. C. (Asia Pacific Education Review, 2018)
This paper adopts a political economy perspective in understanding how the country context frames the development of higher education doctoral science, technology, engineering, and mathematics (STEM) programs. We argue that a country's commitment to research and development spending as a strategy to maintain its economic competitiveness creates the market for research labor. This embeddedness of STEM doctoral training programs in the country's science and technology system enlarges differences between STEM and non-STEM doctoral programs. This argument is validated from a survey of doctoral students in leading Pacific Asian universities which shows that STEM doctoral programs have stronger research networks, are better financed, use better facilities, and incorporate a variety of research placements. The embeddedness of STEM programs is further illustrated from the case of Singapore. Singapore-based STEM doctoral students mention enjoying better financial support and receiving better career advice from their supervisors. They depend on collaborative peer learning and cite more varied employment options when asked about their career plans.
Keywords: Career Counseling; Cooperative Learning; Doctoral Programs; Educational Facilities; Employment Opportunities; Financial Support; Foreign Countries; Graduate Students; Networks; STEM Education; Student Attitudes; Student Placement; Student Research; Student Surveys; Supervisor Supervisee Relationship; Universities

Building essential life skills through visual arts in the early years education - Goitia, Isabel Maria Marçal da Silva (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Financial valuation of Las Vegas Sands Corp - Gomes, Sérgio (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

DISRUPT - Environmental Endocrine disruptors: Current situation in Macao, neurobehavioral effects and bioremediation strategies - Gonçalves, David (University of Saint Joseph, 2018)

FIGHT – Hormonal, pheromonal and genomic regulation of aggression in a fish model - Gonçalves, David (University of Saint Joseph, 2018)

Aesthetic experiences with young children in Hong Kong - Ho, C.K.L. (Meaning making in early childhood research: Pedagogies and the personal, 2018)

Adolescent pathways to hikikomori in Macau - Hon, Leng Ian (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family constellations: a systematic review and a critical analysis - Kuan, Man Sok (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

Communication between Chinese and Portuguese communities: case study of Macau - Lai, Chi Kei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

User intention to adopt mobile payment services in Macau - Lam, Ka Wai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Adaptive music composition for ballet fundamental training barre and center practice - Lam, Man Yin (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Multi-view Convolution Neural Network with Swarm Search Based Hyperparameter Optimization for Enhancing Heart Disease and Breast Cancer Detection - Lan, K.; Li, T.; Fong, S.; Marques, J.A.L.; Wong, R.K. (5th International Conference on Soft Computing and Machine Intelligence, ISCMI 2018, 2018)

Improvement in English learning by using a systematic learning approach in reading comprehension: a case study in primary school of Macau - Lao, Wai Man (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

Newman and the Ministerial Priesthood - Law, Cyril Jerome (Friends of the Ordinariate, 2018)

The OBOR Global Geopolitical Drive: The Chinese Access Security Strategy - - Leandro, F. J (Law, Economics, and Politics, 2018)

The OBOR geopolitical drive: the Chinese access security Strategy - Leandro, Francisco J. B. S. (The Belt and Road Initiative Law, Economics, and Politics, 2018)

Steps of Greatness: Geopolitics of OBOR, Ed. University of Macau. - Leandro, Francisco José (University of Macau, 2018)

An analysis of teacher questions and student responses in a primary school in Macau: a case study - Lee, Soo Mi (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A financial evaluation of MGM Resorts International - Lei, Cheng I. (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Perception and insight on the psychological and environmental risk factors contributing to first time drug use among young adults in Macau - Lei, Hon Nei (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Three Essays on Foreign Trade, Offshoring and International Rivalry - Lei, Weng Chi (University of Washington, 2018)
This dissertation consists of three essays, covering the topics of foreign trade, offshoring and international rivalry. In particular, Chapter 1 analyzes the strategic capacity allocation of an international oligopoly. Because a line of products shares specific inputs that are fixed in the short run, a multiproduct oligopolist faces a capacity constraint in the production. Not being able to produce the desirable quantities to meet demand, an oligopolist strategically allocates its capacity among different products against its rival. If the market were monopolistic, a firm would mainly concern the effective profitability of a product when allocating its capacity and when responding to a capacity expansion. Identical duopolists that compete in a Cournot fashion should have identical capacity allocation. However, in a sequential game, while the Stackelberg leader allocates all its scarce capacity towards the more profitable product, the follower should still allocate some capacity towards the unprofitable product. This matches the observation that Boeing, the incumbent in the large commercial aircrafts (LCA) industry, specializes in smaller planes, while Airbus allocates resources more evenly towards both superjumbo planes and smaller planes. Chapter 2 provides an explanation to the observation that international oligopolists, which are similar in many ways (subject to the same state of technology, have equal market shares, etc.), may engage in significantly different degrees of offshoring. Different from previous studies, which considered fragmentation to be affected by global exogenous factors only, this essay sees fragmentation as an endogenous variable. A firm can invest on R&D of its own fragmentation technology to enable certain degrees of fragmentation, so that offshoring of those fragmented subparts can be achieved. An important implication of endogenous fragmentation is that the government now has a policy alternative to export subsidy. Very often, when export subsidy is prohibited under an FTA, a government has incentive to subsidize fragmentation of a firm, which can stimulate both export and offshoring. Chapter 3 investigates Macao's and Singapore's questionable goal to diversify among two tourism services—gambling and convention. Macao has a cost advantage in gambling while Singapore has a cost advantage in convention. When a city operates as a regional monopoly, the simple multiproduct model shows that it is optimal for a city to diversify in response to an expansion in the markets of the tourism services. If the two cities operate as a Cournot duopoly instead, there will be a higher degree of product differentiation between the cities. Yet, both cities diversify more when there is a market expansion. On the other hand, Osaka is a potential entrant. The three-city model shows that if Osaka's relative cost of producing convention is even lower than Singapore’s, both Macao and Singapore will produce greater proportions of gambling compared to the two-city case. In general, Macao and Singapore respond to Osaka’s rivalry by strategizing their product mixes to avoid head-on competition with Osaka.
Keywords: 0501:Economics; Economics; Foreign trade; International rivalry; Offshoring; Social sciences; Strategic capacity allocation

Conceptions of giftedness in Macau - Leong, Nga Ut (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A study on customer loyalty and Japanese Ramen specialty restaurant - Leong, Tek Kei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Community attitudes on disability: an analysis of disability discourse in Macao newspapers - Leong, Weng Ka (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Fast Cluster-learning with Prior Probability from Big Dataset - Li, Tengyue; Fong, Simon; Lobo Marques, Joao Alexandre; Wong, Raymond K. (2018 5th International Conference on Soft Computing & Machine Intelligence (ISCMI), 2018)
Association Rule Mining by Aprior method has been one of the popular data mining techniques for decades, where knowledge in the form of item-association rules is harvested from a dataset. The quality of item-association rules nevertheless depends on the concentration of frequent items from the input dataset. When the dataset becomes large, the items are scattered far apart. It is known from previous literature that clustering helps produce some data groups which are concentrated with frequent items. Among all the data clusters generated by a clustering algorithm, there must be one or more clusters which contain suitable and frequent items. In turn, the association rules that are mined from such clusters would be assured of better qualities in terms of high confidence than those mined from the whole dataset. However, it is not known in advance which cluster is the suitable one until all the clusters are tried by association rule mining. It is time consuming if they were to be tested by brute-force. In this paper, a statistical property called prior probability is investigated with respect to selecting the best out of many clusters by a clustering algorithm as a pre-processing step before association rule mining. Experiment results indicate that there is correlation between prior probability of the best cluster and the relatively high quality of association rules generated from that cluster. The results are significant as it is possible to know which cluster should be best used for association rule mining instead of testing them all out exhaustively.
Keywords: Association Rule Mining; Big Data; Clustering; Clustering algorithms; Data mining; Itemsets; Preprocessing; Prior Probability; Probabilistic logic; Probability distribution

Artificial intelligence and forensic computing - Lobo-Marques, J. Al (Forensic Computing, 2018)

German restaurant adoption in Macau - Loi, Sio Mei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Evaluating the relationship of Filipino domestic helpers and their employers: towards improving inter-cultural community development in Macao - Lok, Weng I. (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Assessing driving behavior in Macau public transportation through mobile crowd sensing - Ma, Fei Chun (University of Saint Joseph, 2018)
This thesis introduces, implements and evaluates an innovative concept for assessing driving behavior in public transportation through Mobile Crowd Sensing (MCS), under the field of Advanced Public Transportation System (APTS) - a sub-group of Intelligent Transportation Systems (ITS). Aggressive driving behavior is known to be a cause of avoidable accidents and to increase fuel consumption. In public transportations, it is also a case for costumers’ dissatisfaction. Monitoring the quality of driving behavior is a key element to overcome this issue and to improve road safety and customer satisfaction. In this research project, a software application (app) for mobile devices was developed as an experimental tool / proof-of-concept, to monitor aggressive driving behavior in bus drivers, collecting data coming from mobile device’s accelerometer and passengers’ qualitative evaluation. The experimental procedure took place in public transportation in Macau (bus only) and consisted of data collection of drivers’ aggressive driving behavior using the developed application. The analysis of collected data suggests that MCS is a viable way to assess drivers’ behavior in public transportation, thus contributing to the improvement of the service and increase of road safety. Although the methodology has been tailor-made for Macau public transportation, it is believed that the same concept can be applied to other cities, leading them towards the goal of becoming smarter cities. Keywords: driving behavior; mobile crowd sensing; crowdsourcing; smart city; advanced public transportation system; intelligent transportation system; road safety; mobile device accelerometer
Keywords: Thesis and Dissertations PhD in Information System (D-IS); University of Saint Joseph

Effects of parenting styles, parent expectations, and academic results on Macau adolescent's self-esteem - Mak, Chi Kwan (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The multidimensional impact of foreign direct investment on host country economic development: a case analysis of Mozal Aluminum Smelter in Mozambique - Manhiça, Laura Antuérpia Francisco (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Cyberculture and Multimodal Digital Games in Learning Environments: Fostering Creativity in Macau’s Educational System - Martins de Abreu, F.; Barbosa, Alvaro (LISBON CONSORTIUM - VIII Lisbon Summer School for the Study of Culture “Cyber+Cipher+Culture", 2018)

Creating multiculturalism amidst ethnic, linguistic and religious diversity: a Filipino perspective. - Monera, Arnold (Multiculturalism in Asia – Peace and Harmony, 2018)

Translation into Portuguese of the work Macau Days - a tri-lingual book (English, Portuguese, Chinese) that includes a series of poetic texts by Brian Castro and artworks by John Young, 2017 in collaboration with the J.M. Coetzee Centre for Creative Practice and the EU Centre for Global Affairs, University of Adelaide, Australia. - Morais, I. (A-A-Publishing, 2018)

Macao Caught between the "Tropical China" and Oriental-style: An Approach to the Colonial and Post-colonial Contexts/Macau entre a "China Tropical" e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pos-colonial/Macao entre la "Chine tropicale" et la lusophonie a l'orientale: contribution a l'etude des contextes colonial et post-colonial. - Morais, Isabel (Portuguese Studies Review, 2018)
Gale OneFile includes Macao Caught between the "Tropical China&q by Isabel Morais. Click to explore.

Macau entre a “China Tropical” e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Portuguese Studies Review, 2018)

Macau entre a ‘China Tropical’ e a Lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Novas perspetivas sobre o luso-tropicalismo, Portuguese Studies Review PSR, 2018)

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)

Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.

Project management methodologies: an effectiveness analysis of PMBOK and Agile on Macau's Construction Industry - Morais, João Jose Bragança dos Reis de (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Implementing cross-curricular themes - Morrison, Keith (2018)

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

Exploring service quality in luxury retail in Macau - Mui, Wing Yan (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (Advances in Geospatial Technologies, 2018)

Evaluation of Deterministic Spatial Interpolators with myGeoffice©: The Utah Grasshoppers Case - Negreiros, Joao; Phillips, Jenny O. L. (International Journal of Geology, Agriculture and Environmental Sciences, 2018)
The knowledge of spatial distribution of grasshoppers can be very relevant for agricultural planning purposes. On the other hand, the comparison of spatial interpolators for efficiency and reliability reasons is also a key factor to understand interpolation maps outcomes (versus reality). At last, but not least, the use of open Web geographical tools to disseminate true spatial inferential methods to address spatial issues is still quite limited (if none) in high schools and universities, particularly in Geography subjects. If the latter can be addressed with myGeoffice©, the first issue will use the Utah, USA, dataset (58 samples) to layout the spatial distribution of grasshoppers and understand the counties that are more pro to this kind of agriculture infestation. Inverse Distance Weighted (IDW), Moving Average (MA), Multi-quadratic, Inverse Multi-quadratic and Nearest Neighbor (NN) will produce interpolated surfaces of grasshopper’s properties. Efficiency of spatial interpolators was assessed in this writing based on the prediction error’s statistics derived from the difference between the estimation and the real samples on a cross-validation procedure. Remarkably, results show that NN was the most accurate one when compared with the remaining deterministic approaches at sample’s locations.

Portuguese as an Additional Language: Domains Use among Young Learners - Neves, Ana Cristina (Language Policy and Language Acquisition Planning, 2018)
Three key concepts will make up the pillars of this paper: second, foreign and heritage languages. Whenever appropriate “additional language” will be used as an umbrella term. A study of the domains of language use will be applied to these three different sociolinguistic contexts. To date, there are not many empirical studies on the domains of language and, more specifically, among young learners in different areal contexts, as it is the case of this study.
Keywords: Additional language; Domains of language use; Foreign language; Heritage language; Language policy; Second language

Open Innovation as Means of Building Social Capital: A Way to Globalization for Traditional SMEs - Phillips, Jenny O. L. (Journal of Strategic Innovation and Sustainability, 2018)
This research explores innovation of traditional SMEs that do not actively invest in innovation. Elements of open innovation have been identified in these firms in their effort to build social capital which they perceive as pertinent to their businesses. The result of the research shows that instead of using social capital as means for innovation, the unintentional practice of open innovation has contributed to the development of social capital, which further opens up potential for globalization. As a result, a model of open innovation as means of developing social capital for enhancing globalization potential for SMEs was developed.
Keywords: Innovation; SMEs; Social Capital; Sustainability

Transgenerational Entrepreneurship In Chinese Family Businesses: Proposal For A Model Of Work-Life Synergy - Phillips, Jenny O. L.; Osorio, Arturo E.; Alves, José (2018)
Family business are the dominant form of business in the world, and Chinese family business (CFB) is a unique type of family business that relies on collective action to survive. This paper argues that in CFBs, entrepreneurial actions are transgenerational collective endeavors, and successors are groomed as stewards of the family legacy. Work-life relationship in CFBs is about synergy and not balance because the family identity is the business identity, and vice-versa. Using five in-depth case studies, this research introduces an alternative understanding of CFBs and proposes a model of work-life synergy in transgenerational entrepreneurship based on discussion of five theory-based propositions. This model explains that through emphasizing on the business family's shared value and entrepreneurial legacy, elements of trust, shared identity and stewardship of family members are enhanced which leads to collective action and goal of the business family, resulting in transgenerational entrepreneurship. Limitations and future research are presented.
Keywords: Chinese family business; family legacy; stewardship; transgenerational entrepreneurship; work-life synergy.

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny Oliveros Lao (University of Saint Joseph, 2018)
This dissertation reports on a study which aims to add to the theoretical understanding of how social capital is transferred from one generation to the next in business families. Studies in the field of family business have emphasized the importance of succession for the survival of family businesses, but while the succession process and planning have been widely studied, the examination of social capital succession is scarce. As for the studies in family business’s social capital, the importance of social capital as a source of competitive advantage which already exists in business families have often been expressed, but there is a lack of research in the means of transferring this form of capital from the family business leaders to their successors. The study presented here addresses this gap in family business succession literature and social capital literature, explaining the means of transgenerational succession of social capital in family businesses. This is a qualitative research using the multiple case study method which aims to investigate the means of social capital transmission by comparing the cases of five different Chinese family businesses in Macau, which are in the succession process, with the successor currently managing the firm while the former generation business leaders are in the process of handing over the business and preparing for retirement. In doing so, this research offers a theoretical framework of explaining how social capital is transmitted from the incumbents to the successors throughout a five-stage succession process developed for this research. The forms of social capital that exists in family businesses are identified from previous literature, in order to clearly explain how these different forms of social capital are passed on from generation to generation based on the review on succession process introduced in published literature. A theoretical iii framework is formed from the two parent theories on family business succession and social capital, and is then verified empirically from five Chinese family businesses in Macau. The cases are developed through in-depth interviews with the incumbents and successors of the family businesses, informal interviews with stakeholders (including family members, business associates, non-family employees and customers), direct observation on the premises of the Chinese family businesses and secondary data, in order to study the process of intergenerational transmission of social capital in these Chinese family businesses
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Early career promotions in hospitality - Phinn, Kan Yean (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Professional Ethics as Training in Civic Education - Rothlin, Stephan (Hong Kong Journal of Catholic Studies, 2018)

Pekinger Nachtgespräche: Gott und die Welt in China (Nighttalks in Beijing. God and the World in China) - Rothlin, Stephan; Achten, Peter (Fromm Verlag, 2018)

The Long March toward Moral Leadership in Business - Rothlin, Stephan; McCann, D (Silliman Journal, 2018)

Content and language integrated learning in higher education: a case study - Santos, Pedro Paulo Pereira Dos (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Reading acquisition in beginner readers: Typical errors in European Portuguese - Simões, Edlia; Martins, Margarida Alves (Educação e Pesquisa, 2018)

A defesa noticiosa do status quo - Simões, José Manuel (E-Revista de Estudos Interculturais, 2018)

O Espaço ao Espaço Público e ao Sentido dos Fatos que os Media nos Oferecem - Simões, José Manuel (Revista GEMInIS, 2018)
Comunicar é tornar comum e informar é dar forma à comunicação. Entre um e outro vai frequentemente uma distancia que nem sempre é possível eliminar. O objetivo deste artigo é mostrar que tanto a comunicação como a informação são um espaço ao sentido da vida. Pese embora as contrariedades e obstáculos, a conivência com os poderes, os imperativos de rentabilidade, a pressão do tempo e a aceleração, os media oferecem um espaço ao espaço público, ao sentido dos fatos, à interpelação; um espaço ao sentido da vida.

What Kinds of Comparison Are Most Useful in the Study of World Philosophies? - Sivin, Nathan; Akasoy, Anna; Anderson, Warwick; Colas, Gérard; Eh, Edmond (Journal of World Philosophies, 2018)
Keywords: comparative history; connected history; cultural manifolds; diachronic; intellectual history; inter-cultural comparison; intra-cultural comparison; mutual pollination; postcolonial history; synchronic; transnational history

A experiência de Macau e Hong Kong – Ensino de Arquitectura entre o Local e o Global - Soares, Nuno (VI Congresso Internacional do Conhecimento Científico ISECENSA, 2018)

ASIA URBAN LAB – Comparative Studio - Soares, Nuno (DATUM: EDU International Education Conference 2018, 2018)

SHAPED BY USE - Mapping, Debating and Envisioning the Customization of Urban Space - Soares, Nuno (AIA (American Institute of Architects) Japan CES Lecture Series, 2018)

The Inner Harbour Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2018)

A financial valuation of Tencent Holdings Limited - Tam, Wai Hou (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Kindergarten and Primary Teachers’ Attitudes Toward Curriculum Reform in Macau. - Tchiang, Isabel (University of Saint Joseph, 2018)

Barriers to financial inclusion: a study of the economic Community of west African states - Té, Adjombi (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
Keywords: Disability; education policy; inclusive education; special education; special education needs

Investigating the urban rulesof the Pearl River Delta: a comparative approach to urban design research and teaching - Tieben, H.; Soares, Nuno; Yiu, E. (IN-TERSECTIONS. Expertise, AcademicResearch and Design from Barcelona, Beirut, Hong Kong, Brisbane, Auckland, Florence, 2018)

The role of spirituality and religion in counseling and pyschotherapy of christian clients - Tse, Chau Hung (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Promoting positive peer pressure through small group peer interaction - Vargas, Maria Chrislina Bondoc (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Listening to the Environment: Importance of Early Acoustic Experience on Hearing and Development in Zebrafish - Vasconcelos, Raquel (University of Saint Joseph, 2018)

A financial valuation of Comcast Corp - Vasu, Kadali (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The development of Jack Ma's e-commerce strategy into the Pearl River Delta Regions - Wong, Cheng (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study and analysis of the Macau press in Chinese language - Wong, Hio In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Postal service in Macao CTT in 2016: a work report of the strategic management of Public Postal Service - Wong, Ho Cheng (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A vignette: study do casual explanation and continuum beliefs affect Macau college students' attitudes towards mental disorders? - Wong, Ka In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parents views on special education in Macao - Wong, Man Wa (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

From digital to Facebook divide: social capital benefits for Facebook immigrant - Yung, Chun Sing (University of Saint Joseph, 2018)
Two billion users make Facebook of academic interest. This thesis creates a Facebook Divide Index, the delineated categories of Facebook Native, Facebook Immigrant, and Facebook Isolate, and develops Facebook inequality concepts. Macau has a fast- growing number of Facebook Immigrants who benefit from using the online social network. Data from participation-observation and surveys demonstrate social capital gain by Facebook Immigrants, with older generation Facebook users relatively happier than their younger counterparts. The thesis concludes that society needs to equip and empower the older generation or Facebook Isolates, so that they can benefit from online social network usage
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

從即興戲劇體驗討論香港幼兒美感教育環境 - 何嘉莉 (亞洲戲劇教育學刊, 2018)